Internet Addiction and Depression among College Students in Malaysia - Othman, Zahiruddin; Chung, Wah Lee (Japan International Cultural Exchange Foundation, 2017)
Introduction: Internet has revolutionized the information age. However, excessive internet use has led to health issues among users and the most commonly reported psychological problem is depression. Yet, there is dearth of research in this area among college students in Malaysia. Objective: The aim of the present study was to examine the internet addiction (IA) and its association with depression and anxiety among college students. Methods: Students age 18-24 from allied health colleges who were doing attachment and posting in Hospital Tengku Ampuan Rahimah, Klang were recruited into the study. IA was assessed using the internet addiction test (IAT), whilst depression and anxiety by using the hospital anxiety and depression scale (HADS) Results: IA was significantly associated with depression (p < 0.001) and male gender (p = 0.047). In addition, IA was also associated with internet use characteristics such as using computer outside home (p = 0.008), using the internet for surfing (p = 0.016) and e-mailing (p = 0.025), and spending more time online during the weekends (p = 0.003). IA was not associated with anxiety (p = 0.365). Conclusions: Internet addiction is associated with depression and male gender among Malaysian college students. Further study on psychological factors such as personality traits and coping styles is recommended in order to understand the underlying mechanism in IA and propose possible interventions